Walt disnep alice in wonderland (Grolier Books Lahore, 2020)
Alice falls down a rabbit hole into the whimsical world of Wonderland, where she encounters a bizarre cast of characters. As she navigates this strange land, she learns to challenge conventions and embrace imagination. The book explores themes of curiosity, identity, and growing up.